COMMON LEARNER STYLES IN FOREIGN LANGUAGE LEARNING (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Foreign language learners have diverse learning styles that influence how they perceive, process, and retain information. Five key dimensions are identified: Sensing vs. Intuitive, Visual vs. Verbal, Active vs. Reflective, Sequential vs. Global, and Cognitive vs. Learning styles. Sensors prefer concrete, structured information; intuitors favor abstract and varied approaches. Visual learners respond to images and diagrams, while verbal learners prefer spoken or written explanations. Active learners learn by doing, reflective learners by thinking. Sequential learners process step-bystep, global learners grasp holistic patterns. Learning styles are shaped by both biology and environment. Effective instruction blends teaching methods to accommodate all learner types.